2007
DOI: 10.1097/01.wnf.0000240951.18821.50
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Double-Blind Trial of a Botulinum Neurotoxin Type A Free of Complexing Proteins

Abstract: NT 201 is effective and safe in inducing the desired paretic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 16 publications
0
59
0
4
Order By: Relevance
“…This prolonged atrophy has been reported previously using electromyographic examinations 16 and from patients surviving botulism. 50 It should be considered when repeated BoNT/A injections are performed into the same muscles because of the vanishing clinical effect after 3-6 (-12) months according to the standard schedule.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This prolonged atrophy has been reported previously using electromyographic examinations 16 and from patients surviving botulism. 50 It should be considered when repeated BoNT/A injections are performed into the same muscles because of the vanishing clinical effect after 3-6 (-12) months according to the standard schedule.…”
Section: Discussionmentioning
confidence: 66%
“…For the preparation XEOMIN 1 published data support a clinical ''one to one'' dose relation of XEOMIN 1 for different dose amounts compared to the preparation of BOTOX 1 (Allergan), 16,48 an assumption which has been doubted recently. 49 However, because all licensed BoNT/A preparations show the same mechanism of action (cleavage of SNAP 25 protein), the described phenomenon within the muscle is not likely to be specific for any BoNT/A preparation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ayrıca 1U Botox, 1U Dysport"a göre 3 kat daha toksiktir 22 . Xeomin dondurularak kurutulmuĢ saflaĢtırılmıĢ ve yardımcı kompleks proteinler (hemaglutinin ve nonhemaglutinin) içermeyen btx-a"dır 2,23,24 . Diğer btx-a ürünlerinden daha az immünojeniktir 2 .…”
Section: Hazırlanıģı Ve ġçErikleriunclassified
“…Comparative studies performed to evaluate efficacy and safety indicated that 1 Botox unit equals 1 unit of Xeomin, 3–5 Dysport and 50–100 Myoblock/Neuroblock units [2, 13, 56, 66, 67]. Results concerning the therapeutic effects of Xeomin are promising; however, those analyzing its biological potency are contrasting [68,69,70]; therefore, further research is required. The lower amount of the included neurotoxin A and the lack of complexing proteins from this product result in its lower antigenicity [71].…”
Section: Pharmaceutical Preparations Of Botulinum Neurotoxinsmentioning
confidence: 99%